Peran stakeholder dalam pengadaan tanah untuk pembangunan Bendungan Bener di kabupaten Wonosobo - Ainun Dwi Rahayu; Reza Nur Amrin (Tunas Agraria, 2022)
The land acquisition for the Bener Dam is carried out as a government project to control water resources and increase the local economy. The analysis is needed to identify stakeholders for a fairer land acquisition mechanism. The purpose of the research is to identify and map stakeholders in the land acquisition process for constructing the Bener Dam in Wonosobo Regency. Data collection was carried out through interviews and direct observation in the field and then analyzed descriptively-qualitatively. The results showed that there were 17 (seventeen) stakeholders divided into 4 (four) quadrants, namely: subject; key players; supporters, and other followers. The roles of stakeholders in the land acquisition activities are policymakers, planners, coordinators, facilitators, implementers, and mediators. The success of land acquisition for development in the public interest is depend on the ability of stakeholders to work together.